Komik Sebagai Refleksivitas Sosial Bangsa Indonesia - Segara, Putu Agung Danu (Jurnal Ilmiah Wahana Pendidikan, 2023)
Comics contain a graphic aspect, illustration is an image art that is used to visually explain an intention or purpose. The purpose of the study of comics as an instrument of social reflexivity of the Indonesian nation is that in the future we should be able to act and make art in the process of nation building in a better direction by not abandoning historical values and national identity. The data in the study of "Indonesian Social Reflexivity Comics" uses a qualitative approach, the data is obtained by reading literacy related to the history of comics in Indonesia. The theory used to analyze Indonesian comics is that the antiquarian approach has the function of finding identity by identifying ourselves with its origins in the past. The author hopes that this research is able to awaken the mentality of the Indonesian people who must adhere to a sense of nationalism and cultural roots, so that the character and identity of the Nation can last forever.